Pengaruh Kualitas Pelayanan dan Lokasi Terhadap Kepuasan Pengunjung Event Digital Creative 2023 - Sitanggang, Aldo Mateus Pesolima; Simbolon, Anggiat Parlindungan (Civiliza Publishing, 2025)
Event Digital Creative 2023 is a convention event organized by the MICE-B Class of 2020 which was held on Saturday, May 13, 2023, the location of this event was held at Pos Bloc Medan. Visitor satisfaction at the 2023 digital creative event is a phenomenon in this study. To provide satisfaction to visitors, there are several factors, one of which is service quality and location. The purpose of this study was to determine the effect of service quality and location on visitor satisfaction at the 2023 digital creative event. The population of this study amounted to 180 and the sample used amounted to 100 respondents. This study uses quantitative research methods with data collection through questionnaires and literature studies. The data results will be analyzed using data quality tests, classical assumption tests, multiple linear analysis, hypothesis testing and determination coefficient tests. The results of this study indicate that service quality and location have a positive and significant effect on visitor satisfaction at the digital creative 2023 event. Simultaneously, service quality and location have a positive and significant effect on visitor satisfaction with a value of 41.9% and the remaining 58.1% is influenced by other factors not examined in this study.